Physiologic, health, and performance responses of beef steers supplemented with an immunomodulatory feed ingredient during feedlot receiving - Lippolis, K. D.; Cooke, R. F.; Schumaher, T. [UNESP]; Brandão, A. P.; Silva, L. G.T. [UNESP]; Schubach, K. M.; Marques, R. S.; Bohnert, D. W. (Oxford University Press (OUP), 2017)
One hundred eight Angus × Hereford steers, originating from 7 cow–calf were obtained from an auction yard on d −2 and transported by road (800 km; 12 h) to an experimental feedlot facility. Upon arrival on d −1, shrunk BW was recorded and steers were grouped with free-choice access to grass hay, mineral supplement, and water. On d 0, steers were ranked by source and shrunk BW and assigned to 1 of 18 pens (6 steers/pen). Pens were allocated to 1) no immunomodulatory ingredient supplementation during feedlot receiving (CON), 2) supplementation with OmniGen-AF (OMN; 22 g/steer daily, as-fed basis; Phibro Animal Health Corp., Teaneck, NJ) from d 0 to 30, or 3) 2 oral capsules of Stocker Immune Primer on d 0 + 15 g/ steer daily (as-fed basis) of Stocker Preconditioned Premix (Ramaekers Nutrition, Santa Cruz, CA) from d 7 to 30 (IPF). From d 0 to 80, steers had free-choice access to grass hay and water and received a corn-based concentrate. Feed DMI was recorded from each pen, and steers were assessed for bovine respiratory disease (BRD) signs daily. Steers were vaccinated against BRD pathogens on d 0 and 21. Final shrunk BW was recorded on d 81, and blood samples were collected on d 0, 3, 7, 10, 14, 21, 31, 42, 56, and 73. Steer ADG and final BW were greater (P ≤ 0.05) in CON steers than in OMN and IPF steers (1.23, 0.76, and 1.06 kg/d [SEM 0.06], respectively, and 320, 282, and 307 kg [SEM 4], respectively) and (P < 0.01) in IPF steers than in OMN steers. No treatment effects were detected (P ≥ 0.76) for BRD incidence (66 ± 4%) and DMI, whereas G:F was greater (P < 0.01) in OMN steers than in CON steers. Mean plasma cortisol concentration was greater (P = 0.01) in CON steers than in OMN and IPF steers. Plasma haptoglobin concentrations tended (P = 0.10) to be greater in CON steers than in IPF steers on d 3, were greater (P = 0.04) in IPF steers than in CON steers on d 7, and tended (P = 0.10) to be less in OMN steers than in IPF and CON steers on d 21. Blood mRNA expression of interleukin 8 was greater (P ≤ 0.05) in OMN and IPF steers than in CON steers on d 3 and in OMN steers than in CON and IPF steers on d 14. Blood mRNA expression of tumor necrosis-α was greater (P ≤ 0.05) in OMN and IPF steers than in CON steers on d 10. Plasma IGF-I concentrations, serum antibody titers to BRD pathogens, and blood mRNA expression of chemokine ligand 5, cyclooxygenase 2, interleukin 8 receptor, and L-selectin did not differ (P ≥ 0.21) among treatments. Collectively, the immunomodulatory feed ingredients evaluated herein impacted adrenocortical and innate immune responses but failed to mitigate BRD incidence and improve performance of receiving cattle.
Keywords: Immunomodulatory ingredients; Innate immunity; Performance; Receiving cattle; Respiratory disease